Climate Change Impacts and Risks for Animal Health in Asia - Forman, S.; Hungerford, N.; Yamakawa, M.; Yanase, T.; Tsai, H. J.; Joo, Y. S.; Yang, D. K.; Nha, J. J. (2012)
The threat of climate change and global warming is now recognised worldwide and some alarming manifestations of change have occurred. The Asian continent, because of its size and diversity, may be affected significantly by the consequences of climate change, and its new status as a 'hub' of livestock production gives it an important role in mitigating possible impacts of climate variability on animal health. Animal health may be affected by climate change in four ways: heat-related diseases and stress, extreme weather events, adaptation of animal production systems to new environments, and emergence or re-emergence of infectious diseases, especially vector-borne diseases critically dependent on environmental and climatic conditions. To face these new menaces, the need for strong and efficient Veterinary Services is irrefutable, combined with good coordination of public health services, as many emerging human diseases are zoonoses. Asian developing countries have acute weaknesses in their Veterinary Services, which jeopardises the global surveillance network essential for early detection of hazards. Indeed, international cooperation within and outside Asia is vital to mitigating the risks of climate change to animal health in Asia.